Birth trauma. Etiology. Pathogenesis. Classification. Clinical manifestations. Diagnostics. Differential diagnostics. Treatment. Preventive measures. Prognosis : methodical recommendations for students of 5th course of medical faculty - Buznytska, O. V.; Voloshin, K. V.; Бузницька, Олена Вікторівна; Волошин, Kостянтин Вікторович (Kharkiv : V. N. Karazin Kharkiv national university, 2018)
Methodical recommendations contains information about etiology. pathogenesis, classification, diagnosis and treatment of birth trauma of the newborn. Soft tissue damage; skull trauma, bone fractures, nerves damage, internal organ hemorrhages are presented. The methodical recommendations were developed on the basis of the Program of the discipline «Pediatrics, сhildren's infectious diseases» for students of higher medical educational institutions of III-IV levels of accreditation, approved by the Ministry of Health of Ukraine. These methodical recommendations are intended for students of the 5th year of English-speaking medical faculties.

Методичні рекомендації містять інформацію щодо етіології, патогенезу, класифікації, діагностики та лікування пологових травм у новонароджених. Представлено ушкодження м’яких тканин; травма черепа, переломи кісток, ушкодження нервів, крововиливи внутрішніх органів. Методичні рекомендації розроблено на основі програми дисципліни «Педіатрія, дитячі інфекційними хвороби» для студентів вищих медичних навчальних закладів III–IV рівнів акредитації, затвердженої МОЗ України. Ці методичні рекомендації призначено для студентів 5-го курсу медичного факультету англомовного навчання.
Родова травма. Етіологія. Патогенез. Класифікація. Клінічна картина. Діагностика. Диференційна діагностика. Лікування. Профілактка. Прогноз : методичні рекомендації для студентів 5 курсу медичного факультету
Навчальне видання
Keywords: MEDICINE; SOCIAL SCIENCES; birth trauma; newborn; cеphalohematoma; clavicular fracture; hemorrhage; пологова травма; новонароджений; кефалогематома; перелом ключиці; крововилив